2020
DOI: 10.3390/ijms21103484
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Binding Induced Folding of Intrinsically Disordered Proteins by Protein Engineering: Caveats and Pitfalls

Abstract: Many proteins lack a well-defined three-dimensional structure in isolation. These proteins, typically denoted as intrinsically disordered proteins (IDPs), may display a characteristic disorder-to-order transition when binding their physiological partner(s). From an experimental perspective, it is of great importance to establish the general grounds to understand how such folding processes may be explored. Here we discuss the caveats and the pitfalls arising when applying to IDPs one of the key techniques to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Such intrinsically disordered regions are common in eukaryotic proteins and important biological functions have been associated with them, such as flexible linker, cellular signal transduction, protein phosphorylation 108,109 . It has been observed that function can arise directly from the disordered state whereas in other cases their function originates from binding-induced folding promoted by other proteins or RNA, DNA molecules 110 . Evidence of EYA3 as an integrator of photoperiodic cues and nutritional regulation was recently found in Atlantic cod (Gadus morhua) 111 .…”
Section: Discussionmentioning
confidence: 99%
“…Such intrinsically disordered regions are common in eukaryotic proteins and important biological functions have been associated with them, such as flexible linker, cellular signal transduction, protein phosphorylation 108,109 . It has been observed that function can arise directly from the disordered state whereas in other cases their function originates from binding-induced folding promoted by other proteins or RNA, DNA molecules 110 . Evidence of EYA3 as an integrator of photoperiodic cues and nutritional regulation was recently found in Atlantic cod (Gadus morhua) 111 .…”
Section: Discussionmentioning
confidence: 99%
“…Φ-analysis has been applied successfully to the folding of transmembrane proteins (Otzen, 2011;Booth, 2012;Paslawski et al, 2015) and includes processes with receptors and gating (Cymes et al, 2002;Mitra et al, 2004;Cadugan and Auerbach, 2007;Aleksandrov et al, 2009;Edelstein and Changeux, 2010). Φ -analysis is particularly useful for studying the folding of intrinsically disordered proteins on binding to folded partners (Karlsson et al, 2012;Dogan et al, 2013Dogan et al, , 2014Rogers et al, 2014;Shammas et al, 2016;Karlsson et al, 2019;Toto et al, 2019;Karlsson et al, 2020;Malagrino et al, 2020;Toto et al, 2020;Karlsson and Jemth, 2021) and for proteins where mechanical force mimics their function in vivo Fowler et al, 2002). It has been extended to RNA folding (Silverman and Cech, 2001;Young and Silverman, 2002;Kim and Shin, 2010;Pereyaslavets and Galzitskaya, 2015) and DNA aptamers (Lawrence et al, 2014).…”
Section: Other Examples With φ-Valuesmentioning
confidence: 99%
“…Therefore, the binding process starts with docking of residues 25À41 of E3 to Im3; subsequently, E3 undergoes structure reorganization (disordered E3) or orientation rearrangement (ordered E3), allowing the N-terminal region to coalesce to the binding site (43). Experimentally, the binding mechanism and involvement of individual residue can be revealed from the f-value measurement (44). Because the tyrosine residue unfolding E3 is located within the hydrophobic core (27,45), it may be possible to carry out mutagenesis at the binding interface for ordered E3 and disordered E3 and measure the corresponding f-values.…”
Section: Binding Simulation Of E3 With Im3 Under the Transition Midpointmentioning
confidence: 99%